2020
DOI: 10.1055/a-1290-8070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prostate MRI Lesion Segmentation Agreement Between Multiple Radiologists and a Fully Automatic Deep Learning System

Abstract: Purpose A recently developed deep learning model (U-Net) approximated the clinical performance of radiologists in the prediction of clinically significant prostate cancer (sPC) from prostate MRI. Here, we compare the agreement between lesion segmentations by U-Net with manual lesion segmentations performed by different radiologists. Materials and Methods 165 patients with suspicion for sPC underwent targeted and systematic fusion biopsy following 3 Tesla multiparametric MRI (mpMRI). Five sets of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
(52 reference statements)
3
14
0
Order By: Relevance
“…Although correctly outlining lesion borders is valuable for treatment planning, determining the presence or absence of abdominal free fluid is the first step in our proposed methodology. The Dice coefficients achieved in this study reflect the difficulty of delineating ascites areas 58 . The low sensitivity can also be attributed to issues with detecting lesions in abdominal parenchymal organs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although correctly outlining lesion borders is valuable for treatment planning, determining the presence or absence of abdominal free fluid is the first step in our proposed methodology. The Dice coefficients achieved in this study reflect the difficulty of delineating ascites areas 58 . The low sensitivity can also be attributed to issues with detecting lesions in abdominal parenchymal organs.…”
Section: Discussionmentioning
confidence: 81%
“…Receiver operating characteristic (ROC) curve, sensitivity, specificity, accuracy, area under the curve (AUC), and average Dice coefficient were included as evaluation metrics. The Dice coefficient is a measure of contour consistency for segmented lesions occupying the same position and can be calculated as: Dice=2XYX+Y#1\begin{equation*} \def\eqcellsep{&}\begin{array}{*{20}{c}} {Dice\; = \frac{{2\left| {X \cap Y} \right|}}{{\left| X \right| + \left| Y \right|}}\;\# \left( 1 \right)} \end{array} \end{equation*}where |X| and |Y | indicate the number of voxels in segmentations X and Y , and X ∩ Y defines the set of voxels that overlap between segmentations X and Y 57,58 . The ascites images after annotation are regarded as a reference and compared with the results of U‐net.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that using DL models can allow for fast and accurate segmentation of MRI images from different scanners [22]. Schelb et al (2020) produced a comparison of prostate MRI lesion segmentation between a DL model and multiple radiologists. The study was performed using MRI images collected from 165 patients suspected to have prostate cancer.…”
Section: Diagnosis Of Prostate Cancer Using Mr Based Segmentation Tec...mentioning
confidence: 99%
“…The authors concluded that smaller segmentation sizes could explain the lower Dice coefficients of the U-Net model. They also discuss how the overlapping lesions between multiple rates can be used as a secondary measure for segmentation quality in future studies [23]. Soerensen et al (2021) performed a study to determine if DL improves the speed and accuracy of prostate gland segmentation from MRI images.…”
Section: Diagnosis Of Prostate Cancer Using Mr Based Segmentation Tec...mentioning
confidence: 99%
“…Recently, deep learning approaches have been proposed for diagnosing patients with suspicion of clinically significant prostate cancer and segment prostate lesions directly from mpMR images [5][8] [19][3] [23]. In addition to evaluating patient-level cancer detection -an image classification problem, results from image segmentation using UNet and its variant [17] have also been reported, as the mpMR-detected lesions may need histo-pathological examination or treatment, for example, through targeted biopsy [10] [13] and focal ablation [2] [15].…”
Section: Introductionmentioning
confidence: 99%